PENGEMBANGAN MULTIMEDIA KOMIK UNTUK MENINGKATKAN SIKAP DAN PRESTASI BELAJAR SISWA (Studi Pada Mata Pelajaran Geografi Kelas X IPS Di SMA Negeri Bengkulu Utara) - Nilla Heryanti; Alexon Alexon (DIADIK, 2021)
The purpose of this research is to produce a comic multimedia product that is feasible as a geography learning medium that improves student learning attitudes, describes an increase in student learning achievement using multimedia comics and describes student achievement using multimedia comics compared to the learning media used so far. The research method used is the research and development method (Research and Development -R  & D-) according to  Brog and Gall. The research  subjects were students of SMAN 11 Bengkulu Utara, SMAN 2 Bengkulu Utara, SMAN 4 Bengkulu Utara, and students SMAN 13 Bengkulu Utara. Data collection techniques in this study were expert assessment sheets, questionnaires and tests. The data analysis technique used in this research was the average score (mean), the percentage score, the Ngain Score and the t-test. This study shows that multimedia comics are suitable to be used as a learning medium in geography learning and the use of comic multimedia can improve student attitudes and learning achievement